2014
DOI: 10.1161/circulationaha.113.006191
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation-Free Survival and Interventions at 3 Years in the Single Ventricle Reconstruction Trial

Abstract: Background In the Single Ventricle Reconstruction (SVR) trial, one-year transplant-free survival was better for the Norwood procedure with right ventricle-to-pulmonary artery shunt (RVPAS) compared with a modified Blalock-Taussig shunt (MBTS). At 3 years, we compared transplant-free survival, echocardiographic right ventricular ejection fraction (RVEF), and unplanned interventions in the treatment groups. Methods and Results Vital status and medical history were ascertained from annual medical record, death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(166 citation statements)
references
References 19 publications
7
159
0
Order By: Relevance
“…More recently, the Single Ventricle Reconstruction Trial found that overall 3-y transplant-free survival in HLHS patients was 64%. Among those who survive to Fontan in the current era, however, 10-y survival is over 90% (5,6). Consequently, focus has turned progressively toward neurologic injury and its effects on neurodevelopmental outcomes in the aging SV population.…”
mentioning
confidence: 99%
“…More recently, the Single Ventricle Reconstruction Trial found that overall 3-y transplant-free survival in HLHS patients was 64%. Among those who survive to Fontan in the current era, however, 10-y survival is over 90% (5,6). Consequently, focus has turned progressively toward neurologic injury and its effects on neurodevelopmental outcomes in the aging SV population.…”
mentioning
confidence: 99%
“…Lower center Norwood volume was associated with sepsis, longer time to first extubation, as well as increased duration of ventilation and length of hospital stay after the stage II procedure (Schwartz et al, 2014). Similarly, lower surgeon volume, but not center volume was also associated with lower three-year transplant-free survival (OR 1.73, 95% CI 1.73 (1.05-2.85), p=0.001) (Newburger et al 2014). This is consistent with our study finding that surgeon volume is a significant predictor of outcomes in our HLHS population with ventricular dysfunction.…”
Section: Surgeon Volumementioning
confidence: 91%
“…However, patients that died pre-Fontan procedure had lower mean RVEF (34 % +/-9 % vs. 43 % +/-7 %) (Newburger et al 2014 1.2.7.6 Association between ventricular dysfunction and mortality in other analyses Ventricular dysfunction was also identified as a risk factor for mortality in other analyses. The spike in moderate ventricular dysfunction incidence seen at three to six months post-Norwood was shown to coincides temporally with the early hazard for death or transplant using the Congenital Heart Surgeons' Society cohort (Wilder, McCrindle, et al 2015b).…”
Section: Ventricular Dysfunction Association With Mortalitymentioning
confidence: 92%
See 2 more Smart Citations